PENYITAAN BARANG BUKTI SEBAGAI PENGEMBALIAN KERUGIAN KEUANGAN NEGARA DALAM PERKARA TINDAK PIDANA KORUPSI OLEH KEPOLISIAN (Studi Kasus di Polrestabes Medan) - Immanuel P Simamora; Syafruddin Kalo; Muhammad Hamdan; Mahmud Mulyadi (USU LAW JOURNAL, 2017)
Abstract Medan Raya Police Department (Polrestabes) part of the Indonesian National Police is located in the region of Medan, North Sumatra province is one of the territorial units (Satwil) under the control of the North Sumatra Police (Poldasu). Medan Polrestabes in the eradication of corruption for its eradication moves in a repressive space, namely investigation. The investigation conducted by Polrestabes Medan aims to ensnare the perpetrators of corruption and confiscate the evidence that is allegedly obtained from corruption or corruption which certainly has economic value so that it will have potential for the return of state losses. That is, the evidence seized by investigators is potentially usurped by the state later through a court ruling and will be used to cover state losses.   Keywords: State Finance, Foreclosure and Corruption